Penerapan Metode PROMETHEE-GAIA Dalam Pemeringkatan Perguruan Tinggi di Indonesia - Ronal Watrianthos; Reti Handayani; Wakhinuddin Simatupang; Dedy Irfan; Mukhlidi Muskhir (STMIK Budi Darma, 2022)
The Ministry of Research, Technology and Higher Education has been conducting university rankings since 2015. The goal is to map or build Indonesian universities. This ranking is known as university clustering, and it is separated into two categories: non-vocational/academic institutions and vocational universities. The goal of this research is to create higher education clusters based on the four key indicators that have been identified. The Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) II decision model in Multi-Criteria Decision Making (MCDM) was employed, together with Geometrical Analysis for Interactive Aid (GAIA) as geometric analysis in the form of decision-making visualization. This investigation yields alternative 2 with a phi of 0.5125 as a compelling value, followed by alternatives 3 and 1. According to the data, the second university out of the five evaluated had the best performance based on the four weights of the Indonesian higher education clustering indicator.